Transport and Urban Development: Two Studies from Johannesburg - Weakley, Dylan; Bickford, Geoffrey (University of the Witwatersrand and Gauteng City Region Observatory, 2015)
This work seeks to quantitatively investigate the relationship between population density and transport in the City of Johannesburg Metropolitan Municipality (CoJ), South Africa. It does so by comparing data from the Gauteng City Region Observatory’s (GCRO) 2011 Quality of Life Survey (QoL) (Gauteng City Region Observatory, 2011a) to population density data from the South African Census 2011. The work finds a correlation between urban population density and the use of different modes of transport in the City of Johannesburg, with private cars used more in lower-density areas, and higher rates of public transport and non-motorised transport use in higher-density areas. The study also compares density and household income to the use of public transport in the city. Across all of the household income categories in the QoL 2011, those living in higher-density areas are more likely to use public transport than those living in lower-density areas. Lastly the paper examines why those living in higher-density areas are more likely to use public transport than those living in low-density areas. The data suggests that cost and walking time to public transport are major factors. On average, walking times to public transport increase as density decreases. Household incomes in higher-density areas are generally lower than those in lower- density areas, and public and non-motorised transport is generally cheaper (in real values) than private motorised transport.
Keywords: transport; urban development; BRT; density